2016
DOI: 10.1111/1468-5973.12130
|View full text |Cite
|
Sign up to set email alerts
|

How Social Media Is Changing Crisis Communication Strategies: Evidence from the Updated Literature

Abstract: By incorporating social media strategies into the traditional framework of crisis communication strategies (CCS), this article presents a comprehensive review of the scholarship on CCS within a global context. Through a content analysis of articles published in 11 journals listed in the Social Science Citation Index (SSCI), 73 articles focusing on the social‐mediated crisis management (SMCM) are identified. Findings show that new strategies such as enhancing and transferring from the organizational perspective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
138
1
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(149 citation statements)
references
References 48 publications
4
138
1
6
Order By: Relevance
“…Social media, as a "double-edged sword" has brought both opportunities and challenges for crisis communication (Cheng, 2016a). On the one hand, scholars found that social media could facilitate organizations to monitor crisis issues, open up-to-date conversations with publics, cultivate critical relationships, and create transparency of organizational actions (Jin & Liu, 2010;Macias, Hilyard, & Freimuth, 2009).…”
Section: Social-mediated Crisis Communication (Smcc)mentioning
confidence: 99%
See 2 more Smart Citations
“…Social media, as a "double-edged sword" has brought both opportunities and challenges for crisis communication (Cheng, 2016a). On the one hand, scholars found that social media could facilitate organizations to monitor crisis issues, open up-to-date conversations with publics, cultivate critical relationships, and create transparency of organizational actions (Jin & Liu, 2010;Macias, Hilyard, & Freimuth, 2009).…”
Section: Social-mediated Crisis Communication (Smcc)mentioning
confidence: 99%
“…In sum, scholars in the past years have increasingly paid attention to the SMCC research in contexts (Cheng, 2016a;Liu et al, 2015;Tai & Sun, 2007;Taylor & Perry, 2005;Zhu et al, 2017). This field also attracted updated reviews from several scholars such as Cheng (2016a), Eriksson (2018), and Rasmussen and Ihlen (2017).…”
Section: Social-mediated Crisis Communication (Smcc)mentioning
confidence: 99%
See 1 more Smart Citation
“…The protests peaked on a Sunday evening, at the end of the third week of protests, on February 5 th , when more than 600,000 demonstrators protested across the country. 4 In the fourth week, the minister of justice resigned as a sign of collaboration and poof that the initiators do not have personal interests or any other hidden agenda.…”
Section: The Eventsmentioning
confidence: 99%
“…(Benoit, 2015;Coombs, 2013. ) Digitaalisen julkisuuden uusi logiikka ja erityisesti sosiaalinen media ovat vaikuttaneet kriisiviestintään ja mainekriisien hallintaan (Cheng, 2016;Goodman, 2017;McCorkindale & Distaso, 2013;Ott & Theunissen, 2015). Nykyisin erilaisilla sidosryhmillä on mahdollisuus tuoda mielipiteensä kuuluviin sosiaalisen median julkisilla areenoilla ja levittää näkemyksiään nopeasti laajoille yleisöille.…”
Section: Kriisiviestintää Vai Kriisivuorovaikutusta?unclassified